Calidad de vida en la ancianidad: más libertad de testar es más justicia - Fernando Ronchetti (Oñati Socio-Legal Series)
This essay is based on whether the restrictions on the freedom to dispose of one’s succession by will, according to the Argentinean Inheritance Law, are accurate in order to protect and enhance life quality of the elderly.